2008
DOI: 10.1080/1086508x.2008.11079656
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Infrared Camera to Improve the Outcome of Facial Nerve Monitoring

Abstract: Intraoperative cranial nerve neuromonitoring (IONM) has significantly reduced morbidity historically associated with skull-base procedures. It provides the surgeon with immediate feedback to preserve both anatomic and physiologic function of monitored nerves. However, when the surgeon cauterizes tissue near the nerve, the monitoring equipment is saturated by the cautery signal, eliminating IONM information at a critical time. The use of an infrared camera under the drapes to observe the face for movement due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…[37] Possible causes may be poor data input due to micro instruments used to cauterise the tissue or tumour surrounding the facial nerve. [34,38] There is also a risk of EMG induced electrical injury by the stimulating probe. This may be minimised by application of pulsed stimulation [39] and the use of monopolar rather than bipolar current.…”
Section: Electromyography Of Facial Nervementioning
confidence: 99%
See 1 more Smart Citation
“…[37] Possible causes may be poor data input due to micro instruments used to cauterise the tissue or tumour surrounding the facial nerve. [34,38] There is also a risk of EMG induced electrical injury by the stimulating probe. This may be minimised by application of pulsed stimulation [39] and the use of monopolar rather than bipolar current.…”
Section: Electromyography Of Facial Nervementioning
confidence: 99%
“…These cameras record under the operative drapes. [38] The camera view is magnified so that even minute movements may be detected by the naked eye. [38] The images are projected on a four-way split screen: Two focus on movements of the facial muscles, another displays the microscopic operating field and the remaining screen projects the EMG tracings.…”
Section: Electromyography Of Facial Nervementioning
confidence: 99%
“…Der Gesichtsnerv hat durch seine Innervation der Gesichtsmuskeln unter funktionellen und kosmetischen Aspekten eine enorme Bedeutung für den Menschen mit erheblichem Einfl uss auf die Lebensqualität [ 11 -14 ] . Die Unfähigkeit der Augenbewegung und ein schiefes Gesicht mit Absenkung des Mundwinkels und der sich hieraus ergebenden Sprechprobleme sowie Schwierigkeiten bei der Nahrungsaufnahme können eine ungeheure Belastung des Patienten bedeuten [ 15 ] . Der Erhalt der Nervus facialis-Funktion ist dementsprechend in der Ohrchirurgie von großer Bedeutung für den Patienten.…”
Section: Nervus Facialisunclassified
“…In particular, incomplete eyelid closure, facial droop and problems with eating, drinking and speaking constitute a heavy burden for the affected patient [15]. Therefore, preservation of facial nerve function is a major aim in ear and lateral skull base surgery.…”
Section: General Preoperative Aspects Of Ear Surgerymentioning
confidence: 99%
“…Animal studies have shown that intermittent stimulation and reduction of stimulus frequency reduce the risk of facial nerve damage, whereas stimulation levels seem to be of minor importance [298], [300], [301], [302], [303], [304]. In recent years, an infrared camera, which allows direct observation of the facial muscles during surgery, has been developed as an adjunct to EMG monitoring [15]. …”
Section: Selected Surgical Proceduresmentioning
confidence: 99%